Functional Outcomes of Symptomatic Implant Removal Following Ankle Fracture Open Reduction and Internal Fixation. (June 2018) - Williams, Benjamin R.; McCreary, Dylan L.; Chau, Michael; Cunningham, Brian P.; Pena, Fernando; Swiontkowski, Marc F.
Background: Orthopedic implant removal following open reduction internal fixation of a fracture is a common procedure, especially in the foot and ankle. The purpose of this study was to evaluate functional change after the removal of symptomatic implants following ankle fracture open reduction internal fixation (ORIF) using the Short Musculoskeletal Function Assessment (SMFA) outcome score. We hypothesized that implant removal after ankle fracture would result in improved functional outcomes. Methods: Retrospective review of prospectively collected data on patients with a closed ankle fracture between 2013 and 2016 was performed. Inclusion criteria were skeletal maturity, symptomatic ankle implants and completion of the SMFA questionnaire prior to and 6 months after removal. Exclusion criteria were development of a nonunion, prior or current infection, peripheral neuropathy or ongoing litigation surrounding the surgery. The primary outcome was change in SMFA score from baseline to follow-up using Wilcoxon signed-rank test. Additional logistic regression models evaluated the effects of age, sex, body mass index, smoking status, and patient American Society of Anesthesiologists scores. Results: The study population consisted of 43 patients. There was a statistically significant improvement in function, represented by a decrease in SMFA scores from baseline to the 6-month follow-up period (∆ = −4.1 [95% confidence interval, −7.0, −1.3]; P = .003). Secondary outcome measures of the bother index and daily activities domain also demonstrated significant improvements ( P = .005 and P = .002, respectively). Additional logistical regression models identified no significant effects by assessed covariates for change in SMFA scores. Conclusion: Patients with symptomatic implants following ankle fracture ORIF had a statistically significant improvement in function following implant removal. There appears to be value in removing implants from the ankle in patients who report discomfort during daily activities. Further investigation into the specific indications for implant removal and the impact of injury and fracture pattern on outcomes is warranted. Level of Evidence: Level IV, case series.